Estimasi Potensi Produksi Rumput Laut di Perairan Nusa Penida Menggunakan Citra Landsat 8 - Made Pande Darmawan; I Dewa Nyoman Nurweda Putra; Widiastuti Karim (Journal of Marine Research and Technology, 2019)
Seaweed is a macroalgae that has many benefits for humans, therefore to meet human needs, seaweed is developed by cultivation. One place for seaweed cultivation in Bali Province is in Nusa Penida Sub-district, which is a water conservation area in accordance with the Decree of the Minister of Marine and Fisheries / KEPMEN KKP No. 24 of 2014. The development of these areas into tourist destinations and the number of seaweed pests and diseases has caused reduced number of farmers who grow seaweed. The data used was secondary data obtained from Department of Marine and Fisheries of Bali Province and field data was taken in February 2018. Landsat 8 imagery that has been corrected by Top of Atmosphere then lyzenga algorithm was included for correction of water columns and then classified the maximum likelihood with coordinate training area, which only classified seaweed classes. The area of seaweed in Nusa Penida using Landsat 8 imagery on February 2018 acquisition was obtained at 69.48 hectares with an accuracy rate of total seaweed of 85.34% and an accuracy of 63.22%. Whereas the estimated results that could potentially be produced in February 2018 were 89,321 tons.